`Have Your Say' in practice: assessing citizens' use of the EU's public consultation platform - Rico Neumann; Sabine Lang; Phillip Meng (European Politics and Society, 2025)
Article 11 of the Treaty on European Union stipulates that the Commission shall consult citizens and civil society. The breadth, frequency, and user-friendliness of consultations have increased considerably since the Lisbon Treaty of 2007 and Better Regulation Agenda of 2015. This study examines the extent to which individual citizens in member states use the consultation process; the policy areas in which they are predominantly active; and the degree to which individual citizen engagement correlates with organizational engagement, including different organizational types. To better understand the conditions that help produce stronger or weaker citizen vis-à-vis organizational responses, we compiled a corpus of more than 850 open public consultations (OPCs) that closed between 2014 and 2021, and randomly selected a subset of nearly 400 OPCs of which approximately 200 reported response data. We find rather low and inconsistent participation rates of citizens, even for consultations in policy areas generally known to rank higher on issue salience as well as substantial dominance of for-profit vis-à-vis individual citizen input. More concentrated citizen activity in Central and Eastern European (CEE) countries might indicate stronger individual commitment in new member states to `have their say' in specific policy areas. Implications for the EU's engagement architecture and democratic model are discussed.
Keywords: 330; citizen participation; European Union (EU); EU legitimacy; participatory democracy; public consultations